Students’ Speaking Anxiety in Delivering Speeches in Indonesian: A Study of First-Semester STIE-SAK Students in the 2025/2026 Academic Year - Padli, Al; Kartawijaya, Sukarta (The Future of Education Journal, 2026)
This study employed a descriptive method, which was considered appropriate for describing the current condition of the research subjects. Descriptive research involves collecting data to test hypotheses or to answer questions regarding the present status of the subject under investigation. The population of this study consisted of all first-semester students in the 2025/2026 academic year. The sample was selected using a total sampling technique, in which the sample was taken in groups. The study involved several classes of STIE-SAK students, namely classes 1M1, 1M2, 1M3, and 1M4, each consisting of 36 students. However, the researcher selected one class as the research subject. To collect the data, the researcher used an observation instrument measuring students’ speaking anxiety in delivering speeches in Indonesian. The observation sheet was completed by the students based on their own responses. Based on the analysis results, it was concluded that, in general, students’ speaking anxiety in delivering speeches in Indonesian showed a negative outcome. The response distribution was as follows: 93 (strongly agree), 138 (agree), 125 (undecided), 116 (disagree), and 23 (strongly disagree). The results were then categorized into positive and negative responses. Positive responses included “strongly agree” and “agree,” totaling 231 responses, while negative responses included “undecided,” “disagree,” and “strongly disagree,” totaling 261 responses. Therefore, it can be concluded that students experience difficulties related to speaking anxiety in delivering speeches.